Šola kot bogato vzgojno okolje - Kukovec, Maja (Sodobna pedagogika, 2025)
Excessive events in schools are nowadays anything but a rarity and amongst other things, they remind us that we are not successful in creating learning environments in which children and adolescents could respectfully express their desires, needs and distresses, actively explore them through relationships with others and learn how to ethicaly (co)exist in the world. Moreover, modern educational trends that rely on measurable, mechanical, and unreflective action, in the name of ensuring a safe and stimulating school, displace from the latter the risk and uncertainty that are necessary for the emergence of ethical subjects. The school has thus found itself in a puzzling position, where the question arises as to when the desire for a safe school becomes dangerous, even non-educational, and how to enable the achievement of the transcendent goals of education, i.e. the emergence of ethical subjects. In this article, we turn to the autopoetic paradigm of education (Luhmann, Medveš) and the concept of subjectification (Biesta) and explore how to strengthen the subjectification potential in school and cope with the awareness that we can never guarantee the the emergence of an ethical subject. As an example of an educational approach that allows us to do this, we turn to peer mediation, where children enter into respectful relationships with others – strangers and through symmetrical communication (co)create school as a dialogical space. Based on this, we also reflect on the current National Programme of Education and encourage discourse on the educational role of schools through the prism of autopoietic education and subjectification.
Keywords: autopoiesis; avtopoeza; dialogic school; dialoška šola; education; kvalifikacija; pedagogika; pedagogy; qualifications; socializacija; socialization; subjektifikacija; sucjectification; vrstniška mediacija; vzgoja in izobraževanje